O fantástico, o maravilhoso e o estranho na composição da figura do narrador em Castelli di rabbia, de Alessandro Baricco - Graziano, Pedro Henrique Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The goal of this research is to clarify how the literary modes Fantastic, Wonderful and Strange, as defined by Ceserani (2006), are important for the composition and valorization of the figure of the narrator in contemporary society in Alessandro Baricco‘s Castelli di rabbia (1991). It‘s believed that the narrator in this work is the one took into consideration by Walter Benjamin (1996), which would be an almost extinct decadent figure due to the arrival of the modernity and the decline of collective experience. The Italian author of this work builds a narrative in which there are several smaller narratives that compose the novel. Each one of these smaller narratives happens inside of a fantastic universe, in which the above-quoted literary modes take place alternately. To study these literary modes, authors such as Furtado (1980), Ceserani (2006), Bessière (1974), and also some considerations of Todorov (1975), pioneering author in this field of study, will be taken into consideration. Each one of the smaller stories narrated have in common the fact that they approach a life goal of some character inside of an imaginary universe, in which the rules of our natural world no longer exist. All these goals are apparently impossible and unreachable, and, however, the characters insist on pursuing them. The goal of this research is to demonstrate how the yen of accomplishment of these goals and the fact that the characters never lose their faith build a strong dialogue with Walter Benjamin‘s conceptions about the narrator and modernity, given that each character narrates his story as well as the ancient ones that preceded this period, in which, according to Benjamin, the art of narrating is about to disappear. The objective of this study is to make explicit how Alessandro Baricco employs the literary modes Fantastic, Wonderful and Weird to revalorize the narrator, creating allegories based on an imaginary universe. In this universe, the characters narrate and share experiences, as well as the narrator defined by Walter Benjamin does. The allegories built have the goal of creating an association between the act of narrating and the act of resisting to the death of narrative and of literature as art, given that after the arrival of bourgeois modernity, literature in general starts to be sold as merchandise. Therefore, literature loses its advisable character, being an object through which it is possible to share experiences. This causes the loss of ancient literary values.

O objetivo desta pesquisa será de esclarecer como os modos literários Fantástico, Maravilhoso e Estranho, como os define Ceserani (2006), são importantes para a composição e valorização da figura do narrador na sociedade contemporânea, em Castelli di rabbia, de Alessandro Baricco (1991). Acredita-se que o narrador presente na obra corpus seja aquele sobre o qual fala Walter Benjamin (1996), que seria uma figura decadente e quase extinta devido ao advento da modernidade e ao declínio da experiência coletiva. O autor da obra corpus, de origem italiana, constrói uma narrativa em que há diversas narrações menores que compõem o corpo de seu romance, e cada uma destas pequenas narrações acontecerá dentro de um universo insólito, no qual se alternarão os modos literários anteriormente citados. Para o estudo dos modos literários, serão utilizados autores como Furtado (1980), Ceserani (2006), Bessière (1974), e também algumas considerações de Todorov (1975), estudioso pioneiro nesta área. Cada uma das pequenas histórias contadas tem em comum o fato de que dizem respeito a um objetivo de vida de um personagem em um universo imaginário, no qual as regras que regem o mundo natural se encontram abolidas. Todos os objetivos são aparentemente impossíveis e irrealizáveis, e, no entanto, os personagens insistem em busca-los. Neste estudo deseja-se mostrar como a ânsia de realização destes objetivos e o fato dos personagens nunca se desencorajarem dialoga diretamente com as ideias de Walter Benjamin e suas considerações sobre o narrador e a modernidade, na medida em que cada personagem narra sua história como faziam os antigos narradores que antecediam a modernidade, período no qual, segundo Benjamin, a arte de narrar está em vias de extinção. Objetiva-se explicitar como Alessandro Baricco emprega os modos literários Fantástico, Maravilhoso e Estranho a serviço da valorização do narrador, criando alegorias a partir do universo imaginário, no qual os personagens narram e compartilham experiências como faz o narrador definido por Benjamin. As alegorias construídas objetivam criar uma associação do ato de narrar com o ato de resistência à morte da narração e do texto literário como obra de arte, visto que a partir da modernidade burguesa, a literatura de modo geral passa a ser vendida como bem de consumo, de modo que perde seu caráter de instrumento através do qual
Il fantastico, il meraviglioso e lo stranno nella composizione della figura del narratore in Castelli di rabbia, di Alessandro Baricco
Keywords: Alessandro Baricco; Castelli di rabbia; Fantástico; Narrativa; Walter Benjamin